Exercise leads to sex-specific recovery of behavior and pathological AD markers following adolescent ethanol exposure in the TgF344-AD model - Reitz, Nicole L.; Nunes, Polliana T.; Savage, Lisa M. (Frontiers in Behavioral Neuroscience, 2024)
Introduction Human epidemiological studies suggest that heavy alcohol consumption may lead to earlier onset of Alzheimer’s Disease (AD), especially in individuals with a genetic predisposition for AD. Alcohol-related brain damage (ARBD) during a critical developmental timepoint, such as adolescence, interacts with AD-related pathologies to accelerate disease progression later in life. The current study investigates if voluntary exercise in mid-adulthood can recover memory deficits caused by the interactions between adolescence ethanol exposure and AD-transgenes. Methods Male and female TgF344-AD and wildtype F344 rats were exposed to an intragastric gavage of water (control) or 5 g/kg of 20% ethanol (adolescent intermittent ethanol; AIE) for a 2 day on/off schedule throughout adolescence (PD27-57). At 6 months old, rats either remained in their home cage (stationary) or were placed in a voluntary wheel running apparatus for 4 weeks and then underwent several behavioral tests. The number of cholinergic neurons in the basal forebrain and measure of neurogenesis in the hippocampus were assessed. Results Voluntary wheel running recovers spatial working memory deficits selectively in female TgF344-AD rats exposed to AIE and improves pattern separation impairment seen in control TgF344-AD female rats. There were sex-dependent effects on brain pathology: Exercise improves the integration of recently born neurons in AIE-exposed TgF344-AD female rats. Exercise led to a decrease in amyloid burden in the hippocampus and entorhinal cortex, but only in male AIE-exposed TgF344-AD rats. Although the number of basal forebrain cholinergic neurons was not affected by AD-transgenes in either sex, AIE did reduce the number of basal forebrain cholinergic neurons in female rats. Discussion These data provide support that even after symptom onset, AIE and AD related cognitive decline and associated neuropathologies can be rescued with exercise in unique sex-specific ways.